Assessment of plasma Catestatin in COVID-19 reveals a hitherto unknown inflammatory activity with impact on morbidity-mortality - Schneider, Francis; Le Borgne, Pierrick; Herbrecht, Jean-Etienne; Danion, François; Solis, Morgane; Hellé, Sophie; Betscha, Cosette; Clere-Jehl, Raphaël; Lefebvre, François; Castelain, Vincent; Goumon, Yannick; Metz-Boutigue, Marie-Hélène (Frontiers in Immunology, 2022)
ABSTRACT 246 words Introduction Neuroendocrine cells release Catestatin (Cts) from Chromogranin A (CgA) to regulate stress responses. As regards COVID-19 patients (COVID+) requiring oxygen supply, to date nobody has studied Cts as a potential mediator in the regulation of immunity. Patients & Methods Admission plasma Cts and CgA - its precursor - concentrations were measured (Elisa test) in 73 COVID+ and 27 controls. Relationships with demographics, comorbidities, disease severity and outcomes were analysed (Mann-Witney, Spearman correlation tests, ROC curves). Results Among COVID+, 49 required ICU-admission (COVID+ICU+) and 24 standard hospitalization (COVID+ICU-). Controls were either healthy staff (COVID-ICU-, n=11) or COVID-ICU+ patients (n=16). Median plasma Cts were higher in COVID+ than in controls (1.6 [1.02; 3.79] vs 0.87 [0.59; 2.21] ng/mL, p<0.03), with no difference between COVID+ and COVID-ICU+. There was no difference between groups in either CgA or Cts/CgA ratios, but these parameters were lower in healthy controls (p<0.01). Cts did not correlate with either hypoxia- or usual inflammation-related parameters. In-hospital mortality was similar whether COVID+ or not, but COVID+ had longer oxygen support and more complications (p<0.03). Cts concentrations and the Cts/CgA ratio were associated with in-hospital mortality (p<0.01) in COVID+, whereas CgA was not. CgA correlated with care-related infections (p<0.001). Conclusion: Respiratory COVID patients release significant amounts of Cts in the plasma making this protein widely available for the neural regulation of immunity. If confirmed prospectively, plasma Cts will reliably help in predicting in-hospital mortality, whereas CgA will facilitate the detection of patients prone to care-related infections.